Visualization and quantification of tongue movement during articulation: Is ultrasound a valid alternative to magnetic resonance imaging? - Kansy, Julia Katharina; Hoffmann, Jürgen; Mistele, Nicole; Shavlokhova, Veronika; Bendszus, Martin; Heiland, Sabine; Krisam, Johannes; Geschwinder, Anne; Gradl, Johann (Journal of cranio-maxillofacial surgery, 2018)
Background - Quality of life in tumour patients following combined ablative and reconstructive head and neck surgery varies significantly. This is at least partially due to differences in speech and swallowing function. A tool to objectively evaluate articulation by magnetic resonance imaging (MRI) has now been tested alongside ultrasound examination. - Patients and methods - A standardized sequence of phonemes from the German language was established in 20 healthy volunteers and recorded in different planes by MRI and ultrasound. Phonemes were identified through recognition of typical tongue configurations by two different observers. An algorithm for metric analysis of articulation in terms of distances and angles for five extreme points on the tongue (anterior, posterior, cranial and two basal corners) was designed. The findings in these volunteers were subsequently compared with the results of an examination of a tumour patient. - Results - Physiological articulation was visualized and evaluated both by MRI and ultrasound. There was a high intra-class correlation coefficient for measurements between independent observers. Tongue position for certain phonemes was mostly constant in healthy patients of different age groups, with gender-specific differences. In a first comparison, tongue position in a patient with tongue cancer differed significantly from this position, both pre- and postoperatively. In agreement with clinical articulation quality, the tongue position of the patient returned to almost normal within 12 months postoperatively. - Conclusion - Both ultrasound and MRI are appropriate instruments for visualization of articulation and objective measurements to evaluate speech in tumour patients. Whilst MRI is more precise and can identify more subtle differences, ultrasound is a valid alternative due to its wider availability and broader applicability.
Gesehen am 04.11.2019